Rapid Assessment in Prey Veng, Cambodia - Ouk, Akhara (International Rice Research Institute, 2022)
The rapid assessment was implemented to characterize the existing groups of farmers (in formal cooperatives or not), and to identify in which groups or sites we can base the Learning Alliances in Prey Veng and Takeo. This was implemented through informal meetings with leaders of cooperatives and groups in the area. The selection is based on groups in drought and flood prone districts, and where groups have linkages with the Provincial Department of Agriculture Forestry and Fisheries.